Selectivity enhancement for higher alcohol product in Fischer-Tropsch synthesis over nickel-substituted La0.9Sr0.1CoO3 perovskite catalysts - Ao, M.; Pham, Gia; Sage, V.; Pareek, Vishnu (Elsevier Ltd, 2017)
© 2017 Elsevier Ltd The performance of La 0.9 Sr 0.1 Co 1-x Ni x O 3 perovskite catalysts with different Ni substitution levels was evaluated in the Fischer-Tropsch (F-T) synthesis for higher alcohol production. It was found that Ni substitution improved the catalyst's reducibility and had a positive effect on higher alcohol synthesis (HAS) from syngas. Only a limited amount of Ni ions can enter into the perovskite structure and then form Co-Ni alloy after reduction. Catalyst characterisation and activity test results indicate that the synergistic effects of the two metal species in the Co-Ni are responsible for the catalytic activity improvement. For high Ni-substituted perovskite catalysts (x = 0.5), the extra-lattice Ni segregates on the catalyst surface and promotes CO methanation during the F-T reaction. A significant deviation of methanol selectivity from the Anderson-Schulz-Flory (ASF) linear distribution was detected for catalysts containing both Ni and Co, suggesting that the alcohol formation mechanism is altered with nickel substitution in La 0.9 Sr 0.1 Co 1-x Ni x O 3 perovskite catalysts. The La 0.9 Sr 0.1 Co 0.9 Ni 0.1 O 3 perovskite catalyst exhibited the highest selectivity towards higher alcohols. The effect of reaction temperature on the catalytic activity is also discussed.